2005
DOI: 10.1097/01.pcc.0000149320.06424.1d
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of plastic bronchitis with aerosolized tissue plasminogen activator in a Fontan patient

Abstract: Treatment of plastic bronchitis with aerosolized tissue plasminogen activator may benefit patients in whom other therapies have failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…tPA can also be useful in animal models for treating a variety of extravascular fibrin deposition disorders, including prevention of intra-abdominal adhesions (49) and clearance of airways after burns and smoke inhalation (50). In addition, it has been reported anecdotally as beneficial therapy for patients with plastic bronchitis after Fontan procedure in congenital heart disease (7,8,10). …”
Section: Discussionmentioning
confidence: 99%
“…tPA can also be useful in animal models for treating a variety of extravascular fibrin deposition disorders, including prevention of intra-abdominal adhesions (49) and clearance of airways after burns and smoke inhalation (50). In addition, it has been reported anecdotally as beneficial therapy for patients with plastic bronchitis after Fontan procedure in congenital heart disease (7,8,10). …”
Section: Discussionmentioning
confidence: 99%
“…Fibrinolytics have proven useful in treating children affected by plastic bronchitis, suggesting that it is the fibrin component that is largely responsible for the obstruction (39)(40)(41). These and other studies (42) were the first to document fibrinogenolysis occurring on a large scale in the airways of asthma patients, but their results still provide little insight into why this harmful phenomenon occurs.…”
Section: Crabs and Clots Provide A Cluementioning
confidence: 96%
“…Whereas long-term, inhaled mucolytic therapy has been relatively safe to use as demonstrated in cystic fibrosis, prolonged inhaled tPA has only been demonstrated without complications in one human case study [63] and therefore should be used with caution. Incubation of removed bronchial casts in solution in vitro with various therapeutic agents and analyzing their efficacy may allow the clinician to individually tailor therapy.…”
Section: Chronic Therapymentioning
confidence: 97%
“…Quasney et al [56] 123 benefit for use of tPA in plastic bronchitis [36,61]. However, there has been reported effective use of inhaled tPA [55,62], and Wakeham et al [63] showed long-term and efficacious therapy over the course of 18 months without any adverse complications. A murine model studied the safety of prolonged, repeated administration of inhaled pulmonary formulation tPA [64].…”
Section: Acute Managementmentioning
confidence: 99%